no , from your lines
-2x/x^2+1=0
-2/x+1=0
at the start you had (x^2 +1) in brackets as I just did
so when you divide top and bottom by x, every term has to be divided by x
and you would get
-2/(x + 1/x) = 0
but I would not do that
If a fraction = 0 , then the zero can only come from the numerator, and the denominator could never be zero, or else we would be dividing by zero
so in
-2x/(x^2+1) = 0
-2x = 0
x = 0
so (0,0) is both an x and a y intercept.
For the given equation list the intercepts.
Y= -2X/(X^2+1)
I think I Have this right I am not for sure?
y=-2x/(x^2+1)
(0)=(-2x/x^2+1)
-2x/x^2+1=0
-2/x+1=0
-2/x+1+0
-2/x*x+1*x=0*x
-2+x=0
x=2
y-intercept
y= -2*0/(0)^2+1
y=o/0^2+1
y=0+1
y=0/0+1
x-intercept:(2,0)
y-intercept:(0,0)
2 answers
ok thanks